Green Marketing dan Quality Brand Sebagai Prediktor Perilaku Konsumen dan Dampaknya Terhadap Keputusan Pembelian Produk - Putu Agus Indra Purnama; Nyoman Rasmen Adi (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACT               The research objective was to find out to determine the effect of green marketing on consumer behavior, influence of brand quality on consumer behavior, influence of brand quality on purchasing decisions, influence of green marketing on purchasing decisions, influence of consumer behavior on purchasing decisions, consumer behavior on the influence of green marketing on decisions purchase, knowing the mediation of consumer behavior on the effect of green marketing on purchasing decisions, knowing the mediation of consumer behavior on the influence of quality brands on purchasing decisions Data collection using semantic difference scale questionnaire. The research method used purposive sampling and accidental sampling using 140 people. Analysis method using SPSS 22. Using AMOS computer application version 22. The results of this study show that green marketing and quality brands have a positive and significant effect on consumer behavior, consumer behavior and brand quality have a positive and significant effect on purchasing decisions, green marketing has a non-significant positive influence on purchasing decisions, consumer behavior can mediate the influence of green marketing and brand quality on decisions purchase at nike.